Development of the immune response in pneumonia due to Staphylococcus aureus (part 2) - A.E. Abaturov; A.A. Nikulinа (Zaslavsky O.Yu., 2017)
The article analyzes the role of pattern-recognition receptors involved in recognition of pathogen-associated molecular patterns of Staphylococcus aureus. There are shown the basic operation of macrophage and monocyte NLRP3, NLRC5, NLRP7, AIM2 inflammasomes that form the active forms of pro-inflammatory cytokines IL-1-beta and IL-18 du-ring the development of pneumonia caused by Staphylococcus aureus.